임상실습을 경험한 보건계열 학생들의 임파워먼트 향상에 영향을 미치는 요인 - 강영한(Yeong-Han Kang); 박종삼(Jong-Sam Park) (한국콘텐츠학회 논문지, 12(7), 2012)
This study aims to suggest proper alternatives of college practice and to do a effective practice in institute of clinical training, through analyze empowerment factors of health-related college students who experienced clinical practice. The scale of empowerment was consisted of self-esteem, self-control, personal control, major career control, morale for major, growth of knowledge and technique. Reliability of scale(Cronbach ${α}$ value) was .944. Factors of health-related college students' empowerment was related to gender(${β}$=-.029), satisfaction to major department(${β}$=.194), satisfaction to supervision(${β}$=.196), and satisfaction practice class(${β}$=.204). As results, to increase empowerment, students have to be content with major and class, supervisor have to make full use of the clinical manual for student and supportive relation with student to be a systematic practice. In college, students have to take an clinical class and sufficient orientations before practice, and assign clinical institution and practical duration that they want. 임상실습을 경험한 보건계열 학생들의 임파워먼트에 영향을 미치는 요인을 실습교육요인과 실습기관요인으로 구분하여 분석함으로써, 학교 실습교육에 대한 올바른 방향을 제시하고, 임상실습기관에서 효율적으로 실습이 이루어지도록 도움을 주고자 하였다. 이를 평가하기 위한 임파워먼트 척도는 자아존중감, 자기통제, 대인통제, 전공진로통제, 전공에 대한 사기, 지식 및 기술적 성장으로 구성되었으며, 척도의 신뢰도 Cronbach's ${α}$=.944로 높았다. 보건계열 학생들의 임파워먼트에 영향을 미치는 요인은 성별(${β}$=-.029), 학과 선택 만족여부(${β}$=.194), 슈퍼비전 만족도(${β}$=.196), 학교실습수업만족도(${β}$=.204) 이었다. 즉 보건계열학과의 학생들의 임파워먼트를 높이기 위해서 학생은 본인의 학과에 만족하며 실습수업에 충실히 임하여야 하고, 슈퍼바이저는 체계적인 실습교육이 될 수 있도록 임상지침서를 충분히 활용하며, 학생들과 지지적인 관계를 형성하여야 한다. 학교에서는 사전에 실습과목이 수강될 수 있도록 하고, 학생들이 원하는 실습기관과 실습기간을 정할 필요가 있고, 실습 전에 충분한 실습 오리엔테이션을 하는 것이 도움이 될 것이다.